On the petrology and geochemistry of jurassic magmatics of the somkheti segment of Somkheto-Karabagh tectonic zone (Northern Armenia) - Gh. L. Galoyan; R. L. Melkonyan; L. S. Atayan; S. L. Chung; R. H. Khorenyan; Y. H. Lee; S. V. Amiraghyan (ՀՀ ԳԱԱ հրատ.)
In the present work the most important attention was paid to the Jurassic magmatic formations of the Somkheti segment of Somkheto-Karabagh (SK) tectonic zone. The results of the petrologic-geochemical studies and U-Pb isotope dating in the magmatic rocks are presented, which have a decisive role in the context of further comparisons. Magmatism took place here in the Middle and Late Jurassic epochs; volcanism has had mainly submarine nature. Ներկայացվում են Սոմխեթի սեգմենտի յուրայի հասակի մագմատիկ ապարներում պետրոլոգաերկրաքիմիական ուսումնասիրությունների և U-Pb իզոտոպահասակային որոշումների նոր արդյունքներ, որոնք ունեն որոշիչ դեր հետագա համադրումների և երկրադինամիկ վերլուծությունների համատեքստում: Մագմատիզմն այստեղ ընթացել է միջին և ուշ յուրայի դարաշրջաններում. Հրաբխականությունը կրել է առավելապես ստորջրյա բնույթ: Приведены новые результаты петролого-геохимических исследований и U-Pb изотопного датирования магматических пород, имеющие решающее значение для палеогеодинамического анализа. Магматизм происходилздесь в эпоху средней и поздней юры, при этом вулканизм имел преимущественно подводный характер.
Keywords: Science; Geology; Tectonics